Black Cumin (Nigella sativa L.) Production Research in Afghanistan - Zahirian, Gul Ahmad (Journal of Natural Sciences – Kabul University, 2022)
Black cumin (Nigella sativa L., Family: Ranunculaceae), an essential plant for spice and pharmaceutical industries, is among the most widely cultivated medicinal and aromatic plants globally. Agricultural practices significantly influence yield and quality in the production of medicinal plants. Black cumin seeds are extensively used in traditional medicine worldwide for the treatment and prevention of various diseases. Black cumin is an annual herb with a broad spectrum of medicinal applications, in addition to its commercial importance as a spice-yielding plant. Prophet Mohammad (Peace Be Upon Him) said, “Use this Black Seed; it has a cure for every disease except death” (Sahih Bukhari). Medicinal plants are considered nature’s gift, and black cumin holds exceptional potential as a safe and effective herbal medicine for human health.